Heifer management characterization in dairy herds from the west of Buenos Aires, Argentina = Caracterização da gestão de novilhas em rebanhos leiteiros do oeste de Buenos Aires, Argentina - Demateis Llera, Federico; Vissio, Claudina; Turiello, María Paula; Herrero, María Alejandra; Larriestra, Alejandro José (School of Veterinary Medicine and Animal Science, University of São Paulo, 2023)
The replacement program in a dairy farm represents the second or third largest cost in a dairy operation. This study aimed to characterize and typify the practices related to the dairy heifer replacement program and describe the growth, development, and health parameters during this period in commercial dairy herds in Trenque Lauquen. A cross-sectional observational study was carried out, including 54 randomly selected dairy farms that were visited once to collect data about facilities and management through a semi-structured survey. Cluster and principal coordinates analysis were applied to classify the farms based on all variables collected, grouped in four main areas: pre-fresh cows, colostrum management, pre-weaning calf ’s management, and personnel. Additionally, growth, development, and health status were also recorded and described for calves and breeding heifers. Two similar-sized farm clusters were identified with differences in management and facilities in different areas of calves rearing. In one cluster there was a greater proportion of farms having a pre-fresh group, implementing appropriate health (colostrum, vaccination) and feeding management. Also, differences in personnel and technical support were relevant. The estimated body gain was 452 and 774 g/d for calves younger or older than 60 d of age, respectively. The age and weight farm averages in breeding heifers were 21.0 mo (range: 16.7-27.5) and 416.3 kg (range: 336.7-519.3), respectively. Diarrhea and respiratory affections were the major problems in pre-weaning calves and heifer rearing, respectively. The median mortality was 7.3, 7.6, and 2.9% at the calving, pre-weaning, and heifer rearing period, respectively. The results showed an improvement opportunity for producers, the design of precise and high impact programs that could lead to an improved replacement program.